Coffee, CYP1A2 Genotype, and Risk of Myocardial Infarction - Cornelis, Marilyn C. (2006)
ontext The association between coffee intake and risk of myocardial infarction (MI) remains controversial. Coffee is a major source of caffeine, which is metabolized by the polymorphic cytochrome P450 1A2 (CYP1A2) enzyme. Individuals who are homozygous for the CYP1A2*1A allele are “rapid” caffeine metabolizers, whereas carriers of the variant CYP1A2*1F are “slow” caffeine metabolizers. Objective To determine whether CYP1A2 genotype modifies the association between coffee consumption and risk of acute nonfatal MI. Design, Setting, and Participants Cases (n = 2014) with a first acute nonfatal MI and population-based controls (n = 2014) living in Costa Rica between 1994 and 2004, matched for age, sex, and area of residence, were genotyped by restriction fragment–length polymorphism polymerase chain reaction. A food frequency questionnaire was used to assess the intake of caffeinated coffee.